(untitled) (Journal of Dhaka National Medical College & Hospital, 2023)
Background: Preeclampsia complicates 2-8% of all pregnancies and it is the most common medical complication associated with increased maternal and infant mortality and morbidity. In Bangladesh about 16% of maternal death occurs due to preeclampsia and eclampsia. Objective: To assess the serum iron level in pregnant women with preeclampsia and normal pregnant women. Methods: A case control study was conducted from January 2015 to December 2015 among 50 patients with preeclampsia as case. The results were compared with 50 apparently healthy pregnant control. Data were collected through the interview. All Statistical analysis done by using SPSS windows package to assess the serum iron level in difference between two groups were evaluated by student’s unpaired t-test. Results: The analysis revealed that serum iron level was significantly (P <0.001) higher in pregnant women with preeclampsia than that of normal pregnant women. Conclusion: In preeclampsia alteration of serum iron status when compared with healthy pregnant women. Excess iron increase lipid peroxidation. Early detection and supplementation to treat this deficiency may reduce the incidence of preeclampsia. J. Dhaka National Med. Coll. Hos. 2023; 29 (02): 24-27